PERBANDINGAN BENTUK -TE IRU DAN -TSUZUKERU SEBAGAI PEMARKAH ASPEK IMPERFEKTIF DALAM BAHASA JEPANG - Elizabeth Ika Hesti Nindya (Diponegoro University, 2017)
-Te iru and -tsuzukeru form are both express the imperfective aspect. Although they both show the continuity of the situation but the situations they exhibit are not exactly the same. In terms of its form -te iru is hojodoushi, while -tsuzukeru is fukugoudoushi. In terms of the meaning, -te iru states the meaning of progressive aspects, habituatif, resultatif, keiken, kiroku, kanryou, while the -tsuzukeru expresses the meaning of continuous, and resultatif.